2019
DOI: 10.12968/bjom.2019.27.2.115
|View full text |Cite
|
Sign up to set email alerts
|

A literature review exploring student midwives' experiences of continuity of mentorship on the labour ward

Abstract: Background Continuity of mentorship is central to students' clinical placement experience. Despite a plethora of studies investigating student-mentor relationships and how it affects grading, limited attention has been paid to the extent to which a lack of continuity of mentorship affects placement experience. Aims To explore the importance of mentor continuity on labour ward for pre-registration midwifery students. Methods A database search was conducted using the terms: ‘student midwives’, ‘continuity’, ‘men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This review identified 3 types of mentoring relationships within 10 eligible studies: (1) student to student (peer), (2) midwife to student, and (3) midwife to new graduate midwife. The majority of reviewed studies were descriptive in nature and published in the United Kingdom, Australia, and New Zealand 13,14,28–34 . One study was published in the United States 4 …”
Section: Literature On Mentoring Within Midwiferymentioning
confidence: 99%
See 3 more Smart Citations
“…This review identified 3 types of mentoring relationships within 10 eligible studies: (1) student to student (peer), (2) midwife to student, and (3) midwife to new graduate midwife. The majority of reviewed studies were descriptive in nature and published in the United Kingdom, Australia, and New Zealand 13,14,28–34 . One study was published in the United States 4 …”
Section: Literature On Mentoring Within Midwiferymentioning
confidence: 99%
“…Hallam and Choucri conducted a literature review of 8 descriptive studies in the United Kingdom and Australia that used different peer mentoring approaches, including group and one‐to‐one mentoring, to evaluate their effectiveness. Students described this relationship as beneficial, as it fostered self‐confidence, established kinship, and helped them experience a sense of connectivity 13 …”
Section: Literature On Mentoring Within Midwiferymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies evaluating the clinical learning experiences of midwifery students have used qualitative and mixed methods research. Topics have included comparisons of clinical supervision methods 17 , clinical placement types 18,19 , and mentorship models 20 . The use of simulation in clinical education 21 and barriers and motivators to learning 22 also feature.…”
Section: Unlike Medicine and Nursing Midwifery Practice As Defined By The International Confederation Ofmentioning
confidence: 99%